2010
DOI: 10.1093/jac/dkq397
|View full text |Cite
|
Sign up to set email alerts
|

Comparative activity of ceftobiprole against Gram-positive and Gram-negative isolates from Europe and the Middle East: the CLASS study

Abstract: ceftobiprole exhibits in vitro activity against a wide range of Gram-positive and Gram-negative pathogens, including multidrug-resistant strains. No changes in its known susceptibility profile were identified.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
12
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 25 publications
3
12
0
Order By: Relevance
“…The high rates of susceptibility to ceftobiprole among MSSA, MRSA, and S. pneumoniae isolates observed in this study are similar to ceftobiprole susceptibility rates reported in a previous study of 9,067 pathogens collected from hospitalized patients across the EU and Middle East in 2008 (CLASS study) 36. In the CLASS study, ceftobiprole susceptibility rates of 100%, 99.9%, and 100% were observed for MSSA, MRSA, and S. pneumoniae , respectively,36 which align very closely with the ceftobiprole susceptibility rates observed in the current study (100%, 100%, and 99.8% for MSSA, MRSA, and S. pneumoniae , respectively).…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…The high rates of susceptibility to ceftobiprole among MSSA, MRSA, and S. pneumoniae isolates observed in this study are similar to ceftobiprole susceptibility rates reported in a previous study of 9,067 pathogens collected from hospitalized patients across the EU and Middle East in 2008 (CLASS study) 36. In the CLASS study, ceftobiprole susceptibility rates of 100%, 99.9%, and 100% were observed for MSSA, MRSA, and S. pneumoniae , respectively,36 which align very closely with the ceftobiprole susceptibility rates observed in the current study (100%, 100%, and 99.8% for MSSA, MRSA, and S. pneumoniae , respectively).…”
Section: Discussionsupporting
confidence: 89%
“…In the CLASS study, ceftobiprole susceptibility rates of 100%, 99.9%, and 100% were observed for MSSA, MRSA, and S. pneumoniae , respectively,36 which align very closely with the ceftobiprole susceptibility rates observed in the current study (100%, 100%, and 99.8% for MSSA, MRSA, and S. pneumoniae , respectively). This suggests that the in vitro activity of ceftobiprole against these prevalent Gram-positive pathogens has not changed in almost a decade.…”
Section: Discussionsupporting
confidence: 87%
“…In particular, for MRSA and pneumococci, MIC 90 values of 2 and 0.5 mg/L, respectively, have been reported, with susceptibility rates consistently exceeding 95% and 99%, respectively ( Table 1). Strains of MRSA resistant to ceftobiprole are uncommon, and usually exhibit an MIC of 4 mg/L, i. e. only two-fold higher than the EUCAST breakpoint for susceptibility (European Committee on Antimicrobial Susceptibility Testing [EUCAST] clinical breakpoint tables, version 9.0, 2019; http://www.eucast.org) [12][13][14][15][16]. Against Enterobacterales, MIC 90 values ≥16 mg/L have been reported, with variable susceptibility rates (Table 1) [12][13][14][15][16][17][18], depending on the prevalence of ESBL and carbapenemase producers.…”
Section: Antimicrobial Properties Of Ceftobiprolementioning
confidence: 99%
“…Ceftobiprole also displays potent activity against Enterobacteriaceae and Pseudomonas aeruginosa isolates that is similar to those of advanced-generation cephalosporins such as cefepime (10)(11)(12)(13).…”
mentioning
confidence: 92%